Geochemical Signature of Mesozoic Volcanic and Granitic Rocks in Madina Regency Area, North Sumatra, Indonesia, and its Tectonic Implication - Zulkarnain, Iskandar (Geological Agency, 2009)
http://dx.doi.org/10.17014/ijog.vol4no2.20094Five samples consisting of two Permian-Triassic basalts, two Triassic-Jurassic granitic rocks, and a Miocene andesite were collected from the Madina Regency area in North Sumatra that is regionally situated on the West Sumatra Block. Previous authors have proposed three different scenarios for the geological setting of West Sumatra Permian Plutonic-Volcanic Belt, namely an island-arc, subduction related continental margin arc, and continental break-up. Petrographic analysis of the Mesozoic basaltic samples indicates that they are island-arcs in origin; however their trace element spider diagram patterns (Rock/MORB ratio) also show the character of back-arc marginal basin, besides the island-arc. Furthermore, their REE spider diagram patterns (Rock/ Chondrite ratio) clearly reveal that they were actually generated in a back-arc marginal basin tectonic setting. Meanwhile, the two Mesozoic granitic rocks and the Miocene andesite reflect the character of an active continental margin. Their spider diagram patterns show a significant enrichment on incompat- ible elements, usually derived from fluids of the subducted slab beneath the subduction zone. The high enrichment on Th makes their plots on Ta/Yb versus Th/Yb diagram are shifted to outside the active continental margin field. Although the volcanic-plutonic products represent different ages, their La/Ce ratio leads to a probability that they have been derived from the same magma sources. This study offers another different scenario for the geological setting of West Sumatra Permian Plutonic-Volcanic Belt, where the magmatic activities started in a back-arc marginal basin tectonic setting during the Permian-Triassic time and changed to an active continental margin during Triassic to Miocene. The data are collected through petrographic and chemical analyses for major, trace, and REE includ- ing literature studies. Â